In Vitro Platelet-Activating Factor Binding Inhibitory Activity of Malaysian Medicinal Plants - Pisar M, Md.; Ali R, Mat (Malaysian Journal of Science, 2005)
The search for new pharmacologically active agents obtained by screening natural sources such as plant extracts has led to the discovery of many clinically useful drugs that play a major role in the treatment of human diseases. As a continuation for a search of platelet activating factor antagonists, a total of 15 methanolic extracts from 12 species of Malaysian medicinal plants were tested in the rabbit platelet membrane receptor preparation for their ability to inhibit PAF binding in vitro. The results demonstrated that five medicinal plants inhibited more than 60% of [³H]-PAF equilibrium binding at the concentration of 200µg/ml.